The interplay of EU Regulation 2019/1111 with the 1980 Hague Convention in matters of child abduction - Biagioni, Giacomo (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Even if Regulation 2019/1111 have a quite limited impact on the EU system of jurisdictional competence and of recognition and enforcement of judgments in matters of parental responsibility, it introduced several novelties with regard to the section devoted to child abduction matters. The adoption of those new provisions suggests to investigate whether this also led to a change in the approach of the Regulation as towards the 1980 Hague Convention. The paper attempts to make it clear that the reference to complementarity can better explain the interplay between the two instruments and that, even more than in the past, the Regulation is not aimed at setting aside the operation of the Convention, but rather at providing special rules for its implementation within the European judicial area.
Keywords: Child abduction; Regulation (EU) 2019/1111; 1980 Hague Convention; protection of fundamental rights; parental responsibility